The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0104-66322008000400008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing conditions on the texture of reconstituted cassava dough

Abstract: -Deformability modulus, hardness, cohesiveness and adhesiveness of cassava dough reconstituted from precooked flour were evaluated using a lubricated compression test and texture profile analysis. Cassava parenchyma processed under different cooking conditions and left at either -5ºC or -20ºC for 24 h was used to make flour, which was reconstituted into dough. As temperature decreased to -20ºC during the storage period of cooked parenchyma, deformability modulus, hardness and cohesiveness of dough increased si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…The differences in the cooking time could be due to differences in the composition of the composite flour used for the pasta preparation. Longer cooking time recorded for the pastas in this study could be due to the use of cassava starch as binder, as cassava dough generally require long cooking time (12–15 min) ( Rodríguez-Sandoval et al., 2008 ).…”
Section: Resultsmentioning
confidence: 93%
“…The differences in the cooking time could be due to differences in the composition of the composite flour used for the pasta preparation. Longer cooking time recorded for the pastas in this study could be due to the use of cassava starch as binder, as cassava dough generally require long cooking time (12–15 min) ( Rodríguez-Sandoval et al., 2008 ).…”
Section: Resultsmentioning
confidence: 93%
“…The samples were dried in an oven (Memmert UF75) for 12 hours at 60°C. Subsequently, the dried precooked cowpea samples were milled into a fine flour (2 mm mesh size) with the aid of a laboratory hammer mill (armfield miller) and packaged and stored as described by Rodríguez-Sandoval et al [23] and Olaniran et al [18] for further use.…”
Section: Production Of Precooked Cowpeamentioning
confidence: 99%
“…While LSF has been used to study deformation and flow behavior of dough food products in several studies, [15][16][17] the procedure has never been considered as a tool to discriminate root, tuber and banana (RTB) genotypes according to their finished food products' texture. Our research provides a novel perspective into the use of texture in discrimination of RTB genotypes as a way to screen them and promote advanced clones for breeding for textural qualities preferred by consumers of RTB food products.…”
Section: Sensory Analysis and Consumer Overall Liking Of Pounded Yammentioning
confidence: 99%
“…13 Bi-extensional viscosity (BEV) is derived based on calculation of force-displacement extension curves into stress-strain data and taking cognizance of geometry of the sample. 14 Several reports are made in the literature on the use of LSF to measure BEV as a tool for quality of wheat dough, 15 cassava dough, 16 steamed bread dough, 17 and mozzarella cheese. 18 To the best of the authors' knowledge, no works have been reported on discrimination of yam genotypes based on extensional texture attributes and finding relationships between instrumental and sensory texture and consumer tests of pounded yam.…”
Section: Introductionmentioning
confidence: 99%